Congratulations to the editors of Endodontics Today Journal on their 20th anniversary! - article Editorial (LLC "Endo Press", 2021)
The "Endodontics Today" journal is a source of scientific and practical research in the field of conservative dentistry, endodontics in Russia. The journal rationally sets itself the task of helping those who are interested in the problems of endodontics, helps them better navigate the current state and the latest trends in its development. The results of modern scientific research make it possible to expand the possibilities of complex diagnostics and treatment of dental diseases. Works reflecting the achievements of domestic and foreign authors are published on the pages of a respected journal. I wish the journal to continue to contribute to the improvement of the professional skills of dentists, to preserve and strengthen the health of the population. New creative successes and a wide audience of readers.Rector of Moscow State University of Medicine and Dentistry A.I. Evdokimova, Honored Doctor of the Russian Federation, Chief Freelance Dentist of the Russian Federation, President of the Society of Physicians of Russia, Academician of the Russian Academy of SciencesDoctor of Medical Sciences, Professor O.O Yanushevich